Legal Protection for Workers with Fixed-Term Employment Agreements (PKWT) Based on a Review of the Job Creation Regulation - Henlia Peristiwi Rejeki; Suriaatmaja, Toto Tohir; Yanto, Oksidelfa (Yayasan Sinergi Kawula Muda, 2025)
One form of employment agreement in Indonesia is a fixed-term employment agreement, or what we usually hear as a contract employment agreement. Recently, more and more business actors or companies have used a contract work system for their workers. It is suspected that in the implementation of the contract work agreement, it is more profitable for entrepreneurs or companies by ignoring the rights of workers that should be obtained. To obtain data, the method used in this study is the library research method, which is a research method carried out in the library, where data is obtained by reading, studying books, laws and regulations, scientific works, papers, the internet and other documents related to this. This article discusses How Legal Protection for workers whose contracts are continuously extended without a clear status. With the ratification of Perpu Number 02 of 2022 which is a replacement for Law Number 11 of 2020 concerning Job Creation, it is hoped that it can help employees with Fixed-Term Employment Agreements (PKWT) to fulfill their rights at work, especially the payment of final PKWT compensation which should be paid when the Fixed-Term Employment Agreement (PKWT) ends.